Investigating the Link Between Glossophobia and Learning Styles: A Mixed-Methods Study in Secondary Education - Zul Astri; Zulfitri Zulfitri; Nurmadina HS (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
Glossophobia, or the fear of public speaking, is a widespread form of social anxiety that can significantly hinder students’ oral performance. This study investigates the relationship between glossophobia and students’ learning styles in the context of classroom speech activities. Employing a mixed-methods design, the research integrates quantitative data gathered through the Taylor Manifest Anxiety Scale (TMAS) and the Barsch Learning Style Inventory with qualitative insights obtained from classroom observations and semi-structured interviews. A total of 41 senior high school students participated in the initial survey, from which 13 individuals identified with moderate to high anxiety levels were purposively selected for in-depth analysis. The findings reveal that visual learners exhibit higher levels of speech-related anxiety compared to other learning style types. These results suggest a potential correlation between learning style preferences and students’ susceptibility to glossophobia. The study emphasizes the pedagogical importance of tailoring instructional strategies to accommodate diverse learning styles as a means of mitigating public speaking anxiety in educational settings.